Grass trimmer handle vibration reduction by imposing node method using vibration absorber. (February 2018) - Patil, Sushil S
The purpose of this investigation is to apply imposing node technique for vibration reduction of petrol engine grass trimmer handle using vibration absorber. The algorithm is devised to find the required resonance frequency of the absorber to impose node at desired location on beam. The numerical simulations are performed to find the usefulness of absorber for imposing nodes at the handle attachment location on timer pipe. The experimental test is conducted to validate the numerical results and to evaluate the vibration suppression during no cutting and cutting conditions. The vibration total value measured at handle of grass trimmer shows that absorber is useful in handle vibration reduction.